CHCHD10 mutations p.R15L and p.G66V cause motoneuron disease by haploinsufficiency - Brockmann, Sarah J.; Freischmidt, Axel; Oeckl, Patrick; Müller, Kathrin; Ponna, Srinivas K; Helferich, Anika Marie; Paone, Christoph; Reinders, Jörg; Kojer, Kerstin; Orth, Michael; Jokela, Manu; Auranen, Mari; et al. (Human molecular genetics, 2018)
Mutations in the mitochondrially located protein CHCHD10 cause motoneuron disease by an unknown mechanism. In this study, we investigate the mutations p.R15L and p.G66V in comparison to wild-type CHCHD10 and the non-pathogenic variant p.P34S in vitro, in patient cells as well as in the vertebrate in vivo model zebrafish. We demonstrate a reduction of CHCHD10 protein levels in p.R15L and p.G66V mutant patient cells to approximately 50%. Quantitative real-time PCR revealed that expression of CHCHD10 p.R15L, but not of CHCHD10 p.G66V, is already abrogated at the mRNA level. Altered secondary structure and rapid protein degradation are observed with regard to the CHCHD10 p.G66V mutant. In contrast, no significant differences in expression, degradation rate or secondary structure of non-pathogenic CHCHD10 p.P34S are detected when compared with wild-type protein. Knockdown of CHCHD10 expression in zebrafish to about 50% causes motoneuron pathology, abnormal myofibrillar structure and motility deficits in vivo. Thus, our data show that the CHCHD10 mutations p.R15L and p.G66V cause motoneuron disease primarily based on haploinsufficiency of CHCHD10.